Accounting regulation and financial reporting quality: pre-and-Post IFRS Nigeria evidence - Jehu, Philip (OMJP Alpha Publishing, 2017)
The purpose of this study is to examine whether accounting regulation is associated with financial reporting quality in Nigeria. Using accrual-based earnings management construct – abnormal accruals as a proxy for financial reporting quality, the study found some significant variation in abnormal accruals with the implementation of International financial reporting standards (IFRS) to regulate accounting practice. Similarly, the research found that the control variables - firm size, leverage, and return on asset have significant effects on financial reporting quality. This study is found to be consistent with previous studies indicating the effectiveness of IFRS adoption in improving financial reporting quality. The study also contributes to the discussion on IFRS adoption across reporting environments. Regulatory agencies in Nigeria might need to consider the combined effect of other corporate governance laws to ensure quality reporting. The study is limited by our sample (2009 - 2014), and by the proxies for both accounting regulation and financial reporting quality, the data of which was in most part handpicked. Future research might consider testing the combined effect of other corporate governance variables like audit committees and board characteristics.